ANALISIS PEMBELAJARAN BERDIFERENSIASI SEBAGAI BENTUK IMPLEMENTASI KEBIJAKAN KURIKULUM MERDEKA - Nurul Halimah; Hadiyanto; Rusdinal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
Differentiated learning is a learning strategy that emphasizes accommodating individual student differences in the learning process. In the context of an independent curriculum, differentiated learning is an effective strategy to accommodate individual student differences. The purpose of this research is to provide a clearer and deeper understanding of differentiated learning as a form of implementation of the Independent Curriculum policy. The research method used in this study is a literature review. Data collection techniques include searching the internet for articles, books, slides, and information. The results of the study show that differentiated learning is a form of independent learning, which is a form of implementation of an independent curriculum that aims to give students freedom in learning according to their learning styles, interests, and ways of learning. By implementing differentiated learning, learning becomes meaningful for students because they are served according to their needs so that they are actively involved in learning and the goals of education can be achieved.